2008
DOI: 10.1007/s11270-008-9944-0
|View full text |Cite
|
Sign up to set email alerts
|

Metal Availability and Chemical Properties in the Rhizosphere of Lupinus albus L. Growing in a High-Metal Calcareous Soil

Abstract: Chemical processes in the rhizosphere play a major role in the availability of metals to plants. The objective of this study was to assess the potential of white lupin (Lupinus albus L.) for the phytoimmobilisation of heavy metals in a calcareous soil with high levels of Zn and Pb (2,058 and 2,947 μg g −1 , respectively) by evaluating the chemical changes in the rhizosphere, relative to bulk soil, which modify the solubility of heavy metals. Plants were cultivated for 74 days in specially designed pots (rhizop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…However, Jeong et al (2012) found that the inoculation of plants with P-solubilizing Bacillus megaterium increased the Cd concentration in B. juncea and Abutilon theophrasti by two folds compared with respective non-inoculated control. Taken together, present and previous research indicating that besides the bacterial metal solubilization activity, the other factors including soil nutrients level, pH, type of metals, plants, etc., greatly influence the metal solubilization in soils and thereby alter its uptake by plants (Martínez-Alcalá et al, 2009;Rajkumar et al, 2013).…”
Section: Influence Of P Myrsinacearum Rc6b On Plant Growth and Metalmentioning
confidence: 99%
“…However, Jeong et al (2012) found that the inoculation of plants with P-solubilizing Bacillus megaterium increased the Cd concentration in B. juncea and Abutilon theophrasti by two folds compared with respective non-inoculated control. Taken together, present and previous research indicating that besides the bacterial metal solubilization activity, the other factors including soil nutrients level, pH, type of metals, plants, etc., greatly influence the metal solubilization in soils and thereby alter its uptake by plants (Martínez-Alcalá et al, 2009;Rajkumar et al, 2013).…”
Section: Influence Of P Myrsinacearum Rc6b On Plant Growth and Metalmentioning
confidence: 99%
“…In Portugal and Spain for instance, there is hardly any information at all on available heavy metals in agricultural soils, and this lack of information is reflected in poorly informed legislation, which does not take soil characteristics into account [17,18]. The initial soil pH and the ability of plant roots to change the pH have been found to be the principal predictors of the exchange of heavy metals, and therefore of their bioavailability [19]. It is generally accepted that anthropogenic heavy metal contamination exists mainly in the form of reactive species on the soil surface, and the concepts of "bioavailability" and "bio-accessibility" were introduced to express the actual effect of the concentration of a contaminant on organisms in the ecosystem [16,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…However, some reports found that with long-term contamination, metals such as zinc (Zn) and cadmium (Cd) did not decrease rhizobial diversity (23) or rhizobial numbers (24). The effects that metals have on microbial diversity and composition (25) depend upon the metal availability, which is influenced by other factors such as climate (26), soil type and structure (27,28), presence of organic matter (29), pH (30), and plant roots (31).…”
mentioning
confidence: 99%